Profile of science research idea of students of elementary school teacher program in basic natural science - Muhammad Syazali; Baiq Niswatul Khair; Aisa Nikmah Rahmatih; Muhammad Erfan; Hasnawati Hasnawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
The purpose of this study is to describe the profile of student science research. The research was conducted on primary school teacher education (PSTE) students at the University of Mataram. The sample consisted of 111 students determined using the purposive sampling method. The data on student science research ideas are in the form of the research titles they propose. The collection is done using the documentation method. A qualitative analysis was carried out using three criteria, namely the suitability of the topic of the diversity of living things, the correctness of the editorial title, and the urgency of the variables studied to determine the quality of each title. Some of the findings in this study include: (1) there are research ideas that are appropriate (64.86%) and not suitable (35.14%) for the topic of the diversity of living things, (2) from the number of titles that are appropriate to the topic, most of them have the right editorial (68.06%), and (3) of the titles that have the right editorial, only 10.20% have the study variables have urgency. Based on these findings, it can be concluded that students' scientific research ideas that have good quality in terms of conformity to the topic of biodiversity, the accuracy of the editorial title, and the urgency of the variables studied are only a small part. However, 44.14% of the overall research ideas can still be continued to the research stage, and writing the results in scientific papers. This conclusion indicates that massive and continuous efforts and real actions are needed to minimize students' shortcomings, weaknesses, and constraints to have sufficient competence or above.